Campomelic dysplasia and malignant hyperthermia. (9th June 2011) - Barros, Andreia; Teixeira, Filomena; Camacho, Maria Carmo; Alves, Cristina
Abstract : Campomelic dysplasia (CD) is a rare clinical entity, usually fatal in the first year of life. It is characterised by bowing and angulations of long bones, along with other congenital anomalies. The occurrence of malignant hyperthermia is rare, but it has been associated with skeletal dysplasias. The authors present the case of a boy, born at 40 weeks of gestational age, with multiple congenital anomalies and subsequently diagnosed with CD, who died at 16 months of age as a consequence of malignant hyperthermia.